The effect of revascularization on lower limb circulation parameters in symptomatic peripheral arterial disease - Gerken, Andreas; Sigl, Martin; Israel, Elisa; Weiß, Christel; Reißfelder, Christoph; Schwenke, Kay (Journal of Clinical Medicine, 2024)
Background: The prevalence of peripheral arterial disease and the number of revascularization procedures performed in symptomatic patients are steadily increasing. However, uncertainties remain regarding hemodynamic monitoring after revascularization and the prediction of clinical outcomes. This study aimed to investigate hemodynamic parameters with a focus on the microvasculature. Methods: This prospective, single-center study included 29 patients (15 with intermittent claudication [IC] and 14 with chronic limb-threatening ischemia [CLTI]). Before and after the revascularization procedure, in addition to the ankle-brachial index (ABI), microperfusion parameters, including microvascular blood flow, capillary oxygen saturation (SO2), and relative hemoglobin content (rHb), were assessed with lightguide spectrophotometry combined with laser Doppler flowmetry using an oxygen-to-see (O2C) device in the horizontal and elevated leg positions. Results: At baseline, SO2 in the elevated leg position was significantly lower in patients with CLTI than in those with IC (p = 0.0189), whereas the other microcirculatory parameters and ABI values were not significantly different. Patients with diabetes mellitus had a higher flow rate than those without in the horizontal leg position (p = 0.0162) but not in the elevated leg position. After successful revascularization, the flow increased immediately and significantly in both positions, whereas SO2, rHb, and the ABI did not. Conclusions: Elevated leg SO2 was significantly lower in CLTI than in clinically compensated peripheral arterial disease, whereas microvascular flow was a suitable surrogate parameter indicating successful revascularization. In studies using surgical or interventional revascularization procedures, noninvasive hemodynamic monitoring of the microcirculation at the foot level might be beneficial.
Gesehen am 09.12.2024